Perspectives on strategies for improving ultra-deep desulfurization of liquid fuels through hydrotreatment: Catalyst improvement and feedstock pre-treatment - Dembaremba, Tendai O.; Majodina, Siphumelele; Walmsley, Ryan S.; Ogunlaja, Adeniyi S.; Tshentu, Zenixole R. (Frontiers in Chemistry, 2022)
Reliance on crude oil remains high while the transition to green and renewable sources of fuel remains slow. Therefore, developing and strengthening strategies for reducing sulfur emissions from crude oil is therefore imperative and makes it possible to sustainably meet the more stringent sulfur level legislations (mostly less than 10 ppm in end-user liquid fuels). The burden of achieving these ultra-low levels of sulfur has been passed to the fuel refiners who are battling to achieve ultra-deep desulfurization through conventional hydroprocessing technologies with refractory sulfur-containing compounds being cited as the main challenge. This is due to several limitations around the performance of the catalysts especially when it comes to refractory compounds. The inhibitory effects of nitrogen-containing compounds (especially the basic ones) is one of the major concerns. Several advances have been made to advance strategies for achieving ultra-deep desulfurization and denitrogenation: improving hydroprocessing infrastructure, improving hydroprocessing catalysts, having additional steps for removing refractory sulfur-containing compounds, improving the quality of feedstocks or adopting other alternative methods. In this work, we provide perspectives that emphasize the importance of further development of hydrodesulfurization (HDS) catalysts and pre-treating feedstocks to remove nitrogen-containing compounds prior to hydroprocessing as promising strategies for achieving ultra-deep hydroprocessing.